Enantioselective recognition of menthol by mouse odorant receptors. Issue 12 (2nd December 2015) - Takai, Yoshiki; Touhara, Kazushige
Abstract: The olfactory system has a remarkable ability to detect and discriminate a vast variety of odorant molecules. In mammals, hundreds to thousands of odorant receptors (ORs) expressed in olfactory sensory neurons play an essential role in this discrimination. Odorants are recognized by ORs in a combinatorial fashion in which a single odorant activates a particular combination of receptors, leading to its perception as a particular aroma. It is well known that enantiomers emit different aromas in spite of exhibiting otherwise identical chemical properties. To elucidate the molecular basis for the difference, we recorded responses to l - and d -menthol in the mouse olfactory bulb and found that enantiomers elicited similar but overlapping and distinct receptor activation patterns. We then identified l -menthol-specific and d -menthol-biased receptors and performed detailed structure–activity relationship studies, revealing high stereoselectivity of the enantiospecific menthol receptor. The binding site on ORs appears to have evolved to distinguish subtle differences in very similar odorant structures. Graphical abstract: : Menthol enantiomers activate a distinct set of odorant receptors, and an enantioselective menthol receptor was identified and characterized in detail.